Highly sensitive electrochemical detection of Hg(II) promoted by oxygen vacancies of plasma-treated ZnO: XPS and DFT calculation analysis. (10th September 2022) - Xie, Feng; Yang, Meng; Song, Zong-Yin; Duan, Wan-Chun; Huang, Xing-Jiu; Chen, Shi-Hua; Li, Pei-Hua; Xiao, Xiang-Yu; Liu, Wen-Qing; Xie, Pin-Hua
Abstract: Even though there have been a variety of electrochemical sensors, it is of great importance to search for a nanomaterial with efficient active sites and explain its mechanism in the electrochemical detection of heavy metals. In the present research work, flower-like oxygen vacancy-rich zinc oxide (OV-ZnO) is prepared by processing flower-like ZnO (ZnO) with plasma. The presence of oxygen vacancies is validated using X-ray photoelectron spectroscopy (XPS), electron spin resonance (ESR), and Raman spectroscopy. The prepared OV-ZnO is then used to modify the glassy carbon electrode (GCE) surface to construct an electrochemically sensitive interface for detecting Hg(II). According to the obtained results, oxygen vacancies can significantly improve the sensing performance of the electrode for Hg(II) detection, achieving a detection sensitivity of up to about 1323.91 μA·μM −1 ·cm −2 and a detection limit of approximately 0.023 μM. In addition, OV-ZnO revealed good anti-interference performance against common heavy metal ions and showed excellent stability and reproducibility. XPS and density-functional theory calculations suggest that its good electrochemical sensing performance could possibly be due to the activation of oxygen vacancies, the low adsorption energy, and the appropriate Hg-Zn bond length. Moreover, the OV-ZnO-modified GCE exhibits high sensitivity to Hg(II) in actual water samples, which offers theoretical guidance for constructing electrochemical sensors for practical applications in the future.